Phenomenology Of Wetonan Tradition In Jarak Village, Plosoklaten, Kediri, Through The Lens Of Islamic Traditionalism - Dewi Nur Asiyah; Zahraini Jannatul Firdaus (International Journal of Religion and Social Community, 2023)
Weton tradition is a tradition to commemorate a person's birthday based on the Javanese calendar with its markets, such as Legi, Pon, Pahing, Wage, and Kliwon. On Weton day, the family will prepare various treats as a form of Gratitude. The meaning of the wetonan tradition is to pray for the baby to avoid danger and be given a long life and blessings. The wetonan tradition is generally carried out when the baby is 35 days old. In Javanese calculations mention selapan. Calculations in the Javanese calendar are also based on a combination of Gregorian calendar calculations and calculations of days in the Javanese calendar. In this study we used the Qualitative Descriptive method. The reason researchers choose Qualitative Descriptive Research is because researchers want to describe the situation that will be observed with Qualitative Descriptive Method is a research method based on facts and there is in fact a natural object and occurs in the village of Jarak Plosoklaten Kediri as the object of research. The purpose of this research is to examine more deeply how the wetonan tradition phenomology that occurs in the village of Jarak Plosoklaten Kediri. The result of this research is all the activities that exist are the meaning of Wetonan Weton or Wetonan Tradition is a birthday party that is held every 35 days. The purpose of the Weton tradition.